The Application of The Game Methods and Interest to Elementary School Studentsâ€™ Learning Outcomes of Fundamental Movement Skills in Running - Rahma Dewi; Bessy Sitorus Pane; Nurkadri Nurkadri; Amirsyah Putra Lubis (Universitas PGRI Palembang, 2023)
This research aimed to determine the application of the game methods and interest to Elementary School studentsâ€™ learning outcomes of fundamental movement skills in running. The research samples consisted of 60 third-grade elementary school students. This research used treatment by level 2x2 research design with Tukey's test at the level of 16Ã¢Ë†Â